2012
DOI: 10.1097/jto.0b013e3182307f62
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of DNA Methylation and the Gene Expression Change in Lung Cancer

Abstract: In conclusion, by combining the whole-genome DNA methylation pattern and the gene expression profile, we identified the six genes (CCDC37, CYTL1, CDO1, SLIT2, LMO3, and SERPINB5) that are regulated by DNA methylation, and we suggest their value as target molecules for further study of SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…Recently, aberrant LMO3 expression in other various types of malignant cells has been reported 27, 28, 29. Our samples examined also did not include any neuronal tissue, so that the further investigation of the LMO3 expression is valuable for understanding its exact role in both normal and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, aberrant LMO3 expression in other various types of malignant cells has been reported 27, 28, 29. Our samples examined also did not include any neuronal tissue, so that the further investigation of the LMO3 expression is valuable for understanding its exact role in both normal and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the Gene Expression Omnibus Profiles of CYTL1 and observed that CYTL1 expression was low in human prostate cancer (GDS1438/219837_s_at/CYTL1), N-methyl-N-nitrosourea-induced rat breast cancer (GDS1363/ 1375001_at/Cytl1), and SP-C/c-raf transgenic mouse lung cancer (GDS3826/1456793_at/Cytl1). Furthermore, CYTL1 was recently reported to be hypermethylated in lung squamous cell carcinoma, and there were typical CpG islands in the CYTL1 promoter (51). Thus, CYTL1 might exert tumor-suppressing effects.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS12 has been shown to be associated with outcome in colorectal cancer [18]; however, to our knowledge this is the first time that ADAMTS12 has been linked to RCC. SLIT2 and LMO3 have been reported to be hypermethylated in pulmonary tumors (another smoking-related cancer) relative to patient-matched normal pulmonary tissue [19] and LMO3 has been shown to have oncogenic potential in neuroblastoma [20]. The SLIT/ROBO pathway is reported to be a therapeutic target for cancer [21].…”
Section: Discussionmentioning
confidence: 99%